Local development and technological innovation in Algeria: experiences and perspectives - Immacolata Caruso (European Regional Science Association (ERSA), 2001)
The starting point of the present paper is the idea that to define a regional development policy which should effectively respond to the new challenges of the future, in particular to the globalisation of the economy and the acceleration of technological changes, it is necessary to think about new methods that grant a privilege to the local solution, using to the maximum the local skills, the national technological strength, the creative and innovative capabilities existents. But, referring to the Mediterranean basin, there are major disparities between regions and countries in the field of innovation and R&D, as also in the level of diffusion of modern information and communication technologies. In particular some Third Mediterranean countries as also some regions of South Europe, if on the one hand have clear difficulties in developing modern forms of industrialisation capable to insure an access to the international markets, on the other need to increase the competitiveness of their firms, to improve their strengths and to compensate the disadvantages due to their periphericity by developing their international contacts with neighbouring countries in the Mediterranean Basin. This study identifies and analyses the policies adopted by Algeria in the development of technological and managerial capabilities to highlight the facilities and the constraints for implementing and managing advanced technology and innovation in the economic lagging regions and to explore ways of innovative co-operation in this field.
Keywords: 330